A randomized controlled trial of a family-based HIV/STI prevention program for Black girls and male caregivers in Chicago: IMAGE study protocol paper - Natasha Crooks; Geri Donenberg; Jessica Ogwumike; Jacqueline Silva; Ebere Udeogu; Emily Pela; Crystal Patil (PLoS ONE, 2025)
Black girls are disproportionately impacted by HIV and STIs in the United States. Black male caregivers are underutilized in family-based HIV/STI prevention programming and offer a novel opportunity to protect Black girls. This study will evaluate the efficacy and implementation of an HIV/STI prevention program delivered to Black girls and male caregivers in community settings. IMAGE: IMARA for the Male Caregivers and Girls Empowerment was adapted from IMARA, an evidence-based mother-daughter intervention to decrease HIV/STI infection and increase communication and healthy relationships among girls and their male caregivers. Using an efficacy implementation design, we will test the effectiveness of IMAGE compared to a time-matched general health promotion program across six community-based organizations. Aim one will evaluate IMAGE in a 2-arm randomized controlled trial with 300 14-18-year-old Black girls and their male caregiver dyads in Chicago, IL. We hypothesize that girls who receive IMAGE will have lower STI incidence (primary outcome), fewer sexual partners, and more consistent condom use (secondary outcomes) at 6- and 12-months compared to girls in the health promotion program. Guided by the 3-Step Implementation Model, our second aim is to identify and describe factors (barriers, facilitators) and processes affecting implementation in community settings. HIV and STI disparities go beyond individual-level factors, and male caregivers may protect girls by being a sexual health resource. This study will facilitate rapid CBO uptake and ownership of IMAGE if effective. Trial Registration: ClinicalTrials.gov NCT06266416